Access to cardiac rehabilitation and the role of language barriers in the provision of cardiac rehabilitation to migrants - Fatima Al-Sharifi; Hanne Winther Frederiksen; Henriette Knold Rossau; Marie Norredam; Ann-Dorthe Zwisler (BMC, 2019)
Abstract Background Cardiac rehabilitation (CR) has proven health benefits and, according to international guidelines, CR must be offered to all eligible patients. Studies have reported lower uptake of CR among migrants, and migrants are known to face several barriers in their access to healthcare, of which language is the most common. The aim of this study is to examine the provision of CR core components for migrants; and the role of language barriers in the provision of CR in Danish hospitals and municipalities. Methods This is a descriptive study based on repeated nationwide surveys conducted in 2013 and 2015 by the Danish Cardiac Rehabilitation Database. The surveys collected information on provision and organization of CR in hospitals (n = 35) and municipalities (n = 98) in Denmark. The survey in 2015 had additional items related to migrants, such as provision of interpreter services and multilingual information material. Results Not all CR core components were provided by hospitals to non-Danish speaking patients. There was no improvement from 2013 to 2015. Hospitals had full coverage (19/19) of interpreter services compared to 84% (26/31) of municipalities. Provision of multilingual information material was low in hospitals 32% (6/19) and in municipalities 3% (1/31). Conclusion This study found language-related barriers in migrants' access to CR, in the form of inadequate provision of CR core components for non-Danish speaking patients at some Danish hospitals and suboptimal provision of interpreter services in municipalities. The findings call for increased attention to language barriers and further studies are needed to map the extent of the problem.